The baby’s not for burning: the abject in Sarah Kane’s Blasted and Helen Oyeyemi’s Juniper’s Whitening - Anita Harris Satkunananthan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Both Sarah Kane’s Blasted and Helen Oyeyemi’s Juniper’s Whitening have frightening instances of theatrical violence which include infanticide. These instances are more overt in Blasted and are alluded to in Juniper’s Whitening. This article interrogates the instances of infanticide within both plays, connecting the violence to the child abuse and farcical infanticide in The Punch and Judy Show. The figure of the child is examined from the perspective of a symbol of civilisation corrupted from within and the murder of the child through the lens of Kristeva’s theory of abjection. The staged infanticide and the rapes present in both texts reflect shifting cultural norms in an increasingly multicultural Britain. The study of these two plays is both literary and dramaturgical; the casual brutality in Kane’s play with the psychological and insidious motifs in Oyeyemi’s work are compared with the motifs found in The Punch and Judy Show and then situated within the context of the In-yerface theatre productions of the 1990s to the 2000s. In both plays, a sense of domesticity being a farce underscoring brutality, torture and infanticide is present.